Copper‐Catalyzed Aerobic CC Bond Cleavage of Lactols with N‐Hydroxy Phthalimide for Synthesis of Lactones. Issue 4 (13th November 2014) - Tnay, Ya Lin; Chiba, Shunsuke
Abstract: The transformation of cyclic hemiacetals (lactols) into lactones has been achieved by Cu‐catalyzed aerobic CC bond cleavage in the presence of N ‐hydroxy phthalimide (NHPI). The present process is composed of a multistep sequence including a) formation of exo ‐cyclic enol ethers by dehydration; b) addition of phthalimide N ‐oxyl radical to the enol ethers followed by trapping of the resulting C‐radicals with molecular oxygen to form peroxy radicals; c) reductive generation of oxy radicals and subsequent β‐radical fragmentation to generate lactones. Abstract : Let′s get physical : A Cu‐catalyzed aerobic CC bond cleavage of cyclic hemiacetals (lactols) into lactones was achieved in the presence of N ‐hydroxy phthalimide (NHPI). This reaction is composed of a multistep sequence including a) formation of exo ‐cyclic enol ethers through dehydration; b) addition of phthalimide N ‐oxyl radical to the enol ethers followed by trap of the resulting C‐radicals with molecular oxygen to form peroxy radicals; c) reductive generation of oxy radicals and subsequent β‐radical fragmentation to generate lactones.